Integrasi Artificial Intelligence dalam Sistem Informasi Web untuk Mendukung Upaya Pelestarian Budaya Sasak Gendang Beleq - Saiful, Muhammad; L M Samsu; Amri Muliawan Nur; Imam Fathurrahman (Jurnal PRINTER: Jurnal Pengembangan Rekayasa Informatika dan Komputer, 2025)
Intangible cultural heritage such as Gendang Beleq, the traditional musical art of the Sasak people in Lombok, faces preservation challenges in the modern era due to the lack of interactive learning resources and the shifting interests of younger generations. This study aims to address these issues by developing a web-based information system that integrates Artificial Intelligence (AI) technology to support cultural preservation and education. The research method includes needs analysis, system design using the System Development Life Cycle (SDLC) model, web application development, and feasibility evaluation. The designed system utilizes AI to automate the creation and presentation of relevant and personalized multimedia content (audio, visual, and text), making the learning materials more engaging and accessible. The trial results indicate that the web information system operates optimally without technical errors and receives highly positive user responses, achieving a feasibility level of 79% as an educational media. These findings suggest that the integration of AI within a digital platform is an effective and feasible innovative approach to enhance young people’s understanding and awareness of the Sasak culture of Gendang Beleq, while bridging conventional preservation methods with modern technology.